Philosophy in the classroom - Lipman, Matthew. (Temple University Press, 1980)
The need for educational redesign. Thinking and the school curriculum. Philosophy. Some educational presuppositions of philosophy for children. The philosophy for children curriculum. Teachingmethodology. Guiding a philosophical discussion. Encouraging children to be logical...